1996
DOI: 10.1080/07481189608252787
|View full text |Cite
|
Sign up to set email alerts
|

Toward a comprehensive model of death anxiety

Abstract: An integrative, comprehensive model of death anxiety is presented. The model postulates three immediate antecedents of death anxiety: past-related regret, future-related regret, and meaningfulness of death. Past-related regret refers to a person's unfulfilled aspirations that should have been achieved but were not. Future-related regret refers to the anticipation that, as a result of premature death, one cannot achieve important goals in the future. Meaningfulness of death refers to one's concept of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
11

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 44 publications
7
92
0
11
Order By: Relevance
“…Empirical research shows that ego integrity and the feeling of a life well-lived, as indicated by life satisfaction and a sense of purpose, are associated with lower death anxiety (see metaanalysis by Fortner and Neimeyer 1999). Thus, some scholars have proposed that death anxiety is a function of the perceived inability to fulfill major life goals, or a sense of regret (Tomer and Eliason 1996). Life regrets are feelings that one is unable to fulfill certain major life goals, which may be due to past errors of omission or commission or the perception that future life circumstances make realizing important goals unlikely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research shows that ego integrity and the feeling of a life well-lived, as indicated by life satisfaction and a sense of purpose, are associated with lower death anxiety (see metaanalysis by Fortner and Neimeyer 1999). Thus, some scholars have proposed that death anxiety is a function of the perceived inability to fulfill major life goals, or a sense of regret (Tomer and Eliason 1996). Life regrets are feelings that one is unable to fulfill certain major life goals, which may be due to past errors of omission or commission or the perception that future life circumstances make realizing important goals unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…Regrets lead to the wish to undo past mistakes and realign actions with goals (Giloviqh and Medvec 1995), but death is a state that rules out the possibility of undoing altogether. Therefore regrets exacerbate the fear of personal mortality (Tomer and Eliason 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death anxiety is an inherently human condition of which we are aware at varying levels of Death Anxiety Resilience 25 our own mortality. This is both a normal and necessary experience that existential psychologists encourage to accept, confront and attribute meaning to our inevitable death [48][49][50]. However due to the overwhelming nature of death anxiety, we attempt to deny this mortality through the use of specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cette densité de publications en fait le champ d'études empirique le plus important de la thanatologie. Certains auteurs se sont essayés à une définition de l'anxiété face à la mort (Tomer et Grafton, 1996). Alors que les premiers travaux présentaient uniquement l'anxiété face à la mort comme un construit unidimensionnel certains souhaitent distinguer aujourd'hui plusieurs sous dimensions (cf.…”
Section: Les Dimensions Psychologiques Et Culturellesunclassified